Foreign models of corporate social responsibility. (Journal of Economic Research & Business Administration, 2016)
Today, the topic of corporate social responsibility (CSR) is becoming more popular in the business community. The variety of existing concepts, approaches and models of CSR in the international practice shows about the extent, which has received the CSR as a phenomenon. The use of various forms of companies and CSR models can not be unified process. Each company has to choose their own path of development and strengthening of the market. However, the knowledge and dissemination of international experience gained can be used to evaluate the tools and the opportunity to impact and prospects of implementation of a particular model.In this regard, the present article examines the CSR model in different countries, identify their similarities and distinctive properties . Particular attention is paid to the peculiarities of corporate social responsibility as one of the most important activities of the company, designed to ensure effective communication of the enterprise, society and the state .
Keywords: corporate social responsibility; small and medium businesses; government incentives; charity; sponsorship; competitiveness.